'Written in Bone': New Discoveries about the Lives and Burials of Four Roman Londoners. (November 2017) - Redfern, Rebecca C.; Marshall, Michael; Eaton, Katherine; Poinar, Hendrik N.
Abstract: The Museum of London selected four individuals for multidisciplinary scientific analyses in order to establish their ancestry, aspects of their personal appearance and health. We also reinterpreted their burial context in order to better understand how identity was constructed and expressed in this unique Roman settlement. Our study discovered the presence of people with Black and White European ancestry, some of whom had migrated from the southern Mediterranean. The most surprising result was that Harper Road woman's chromosomes were male. Overall, our experience of undertaking a multidisciplinary study served to further underline the need for these different techniques to be used in combination when investigating past identities. The mtDNA results were very broad and required the mobility isotopes to better understand their significance, while the aDNA evidence confirmed the osteological analysis. In terms of public engagement at the Museum of London, the ability to determine hair and eye colour had a significant impact.